Emerging Constitutional Strategies - Charters, Claire (Victoria University of Wellington Law Review, 2002)
The author discusses Andrew Butler’s "Limiting Rights", Anthony Lester QC’s "The Magnetism of the Human Rights Act 1998" and Cheryl Saunders’ "Protecting Rights in Common Law Constitutional Systems; A Framework for a Comparative Study" to illustrate that the tension between rights protections and democracy could in fact lead to constructive strategies which protect both democracy and human rights in the future. At first instance, there appears to be a tension between the unilateral enforcement of individuals by the judiciary, and the democratic rights of the whole of society. However, the three papers presented by Butler, Lester QC and Saunders illustrate that comparative analysis shows that society places fundamental value on both. The author concludes that societies should strive to strike the ideal balance between the two.